2011
DOI: 10.1590/s1678-77572011005000006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tissue reaction, cell viability and cytokine production induced by Sealapex Plus

Abstract: ObjectiveThe aim of this study was to investigate the effects of mineral trioxide aggregate (MTA), Sealapex, and a combination of Sealapex and MTA (Sealapex Plus) on the reaction of subcutaneous connective tissue of rats, and on cell viability and cytokine production in mouse fibroblasts. Material and MethodsThe tissue reaction was carried out with dentin tubes containing the materials implanted in the dorsal connective tissue of rats. The histological analysis was performed after 7 and 30 days. Millipore cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…Saline solution and PDT were capable to maintain the cell viability similar to that observed for control during all periods evaluated. These results are similar to previous studies that have showed that PDT did not affect host cell viability from gingival fibroblasts, osteoblasts, and human periodontal ligament cells [22][23][24][25][26][27][28][29][30][31]. On the other hand, disagree with others that have showed that PDT promoting reduction in fibroblast, macrophage and human head [32,33].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Saline solution and PDT were capable to maintain the cell viability similar to that observed for control during all periods evaluated. These results are similar to previous studies that have showed that PDT did not affect host cell viability from gingival fibroblasts, osteoblasts, and human periodontal ligament cells [22][23][24][25][26][27][28][29][30][31]. On the other hand, disagree with others that have showed that PDT promoting reduction in fibroblast, macrophage and human head [32,33].…”
Section: Discussionsupporting
confidence: 85%
“…The cell viability was determined in this study by 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay (MTT) based on the ability of mitochondrial dehydrogenase enzymes in living cells to convert the yellow water-soluble tetrazolium salt MTT into dark blue formazan crystals, a simple method that showed advantages as rapidness and precision [21,22] and the substrate used in the assay does not interfere with measurement end [23]. Complementary, ELISA assay was used for the measured the cytokines secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further clarify the biocompatibility of silver nanoparticles, a model of implantation in the subcutaneous tissue of rats was also used, which is 1 of the most appropriate tests to determine the local effects of compounds (8,33). In the present study, we have analyzed the tissue reaction to SNA and SNP at 1.0 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Outro aspecto que vem sendo estudado é a capacidade dos cimentos endodônticos interferirem na resposta imune (Bernath e Szabo, 2003;De Oliveira Mendes, Ribeiro Sobrinho et al, 2003;Gomes-Filho, Watanabe et al, 2009;Gomes-Filho, Gomes et al, 2011). Associando-se a inflamação já existente fruto do processo patológico à possível irritação ocasionada pelos materiais obturadores, a resposta inflamatória poderá ser persistente mesmo após a obturação (Perassi, Filho et al, 2004).…”
Section: Figuraunclassified